Reformulation of Legal Policy for the Protection of Generation Z from the Threat of Child Grooming: An Islamic Law and Convention on the Rights of the Child Perspective - Innash, Ar-Rahiim; Latif, Muhamad (Institute for Law and Economics Studies, 2025)
Child grooming cases experienced by children in Indonesia, particularly through digital platforms such as Instagram and WhatsApp, reflect the existence of normative gaps (lacunae) in the legal protection system for Generation Z amid the rapid digital era. This crime is carried out covertly and systematically by adults who manipulate victims. This research aims to formulate effective legal policy reforms to tackle the threat of child grooming, referring to the perspective of Islamic Law and the Convention on the Rights of the Child (CRC). This research uses a normative method with legislative, conceptual, and comparative approaches, supported by data in the form of national legal documents, Islamic legal literature (including the concepts of hifzh al-nafs and hifzh al-'irdh), and international legal instruments. The research findings show that national legislation has not explicitly regulated child grooming offenses, thus creating gaps in law enforcement. The scientific contribution of this study is to produce a comprehensive legal framework through synthesis between the principles of protection of honor and life in Islamic Law and the minimum standards of child protection in the CRC. It is concluded that legal policy reform is urgent, which must be realized by explicitly including the formulation of child grooming offenses in legislation. This reformulation not only closes interpretive gaps and ensures legal certainty, but also strengthens legal protection for Generation Z in digital spaces by uniting Islamic philosophical values and international standards